A Note on Improved Homotopy Analysis Method for Solving the Jeffery-Hamel Flow. (30th December 2010) - Motsa, Sandile Sydney; Sibanda, Precious; Marewo, Gerald T.; Shateyi, Stanford
Abstract : This paper presents the solution of the nonlinear equation that governs the flow of a viscous, incompressible fluid between two converging-diverging rigid walls using an improved homotopy analysis method. The results obtained by this new technique show that the improved homotopy analysis method converges much faster than both the homotopy analysis method and the optimal homotopy asymptotic method. This improved technique is observed to be much more accurate than these traditional homotopy methods.